Presence of a functional nitrate assimilation pathway in mycobacterium smegmatis - Khan, Arshad; Akhtar, Shamim; Ahmad, Jawid N.; Sarkar, Dhiman (Microbial Pathogenesis, 2008)
Ability of Mycobacterium smegmatis to assimilate nitrate was evaluated in its active and dormant phase. Nitrate (10 mM), nitrite (0.5 mM) and ammonia (10 mM)allowed growth of M. smegmatis concomitant with their complete depletion from the culture in 144, 120 and 96 h, respectively, when used as sole nitrogen Source. Azide (50 mu M) stopped the growth of M. smegmatis when nitrate was used as sole nitrogen source. L-methionine-S-sulfoximine (L-MSO), which is a well-known inhibitor of glutamine synthetase, an enzyme also involved in nitrogen metabolic pathway, when applied at 10 mu g/ml concentration, completely inhibited the growth of the organism when nitrate or nitrite was used as sole nitrogen source. There was no effect of either azide or L-MSO at above concentrations on the growth of the organism when asparagine or ammonia was used as sole nitrogen source. More significantly, utilization of nitrate, nitrite and ammonia continued even in oxygen depletion induced dormant culture at the rates of 289, 25 and 354 mu M/day, respectively. These rates were 5-8 times slower than the rates of 1966, 127 and 2890 mu M/day, respectively, in active replicating phase. In the presence of azide (50 mu M) and L-MSO (10 mu g/ml), 2.1 and 1.51 logs reduction in viability of dormant M. smegmatis was observed using nitrate and nitrite, respectively, as sole nitrogen source. Altogether, the results indicated the presence of nitrate assimilation pathway operating in both active and dormant stage of M. smegmatis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Dormant bacilli; Glutamine synthetase; L-methionine-S-sulfoximine; Mycobacterium smegmatis; Nitrate assimilation

Method to extract intact and pure RNA from mycobacteria - Akhtar, Shamim; Sarkar, Sampa; Mishra, Abhishek; Sarkar, Dhiman (Analytical Biochemistry, 2011)
We describe a high-yielding, simple, and aerosol-free protocol for the isolation of RNA from mycobacteria that does not require sophisticated instruments. The method yielded 50 mu g of RNA from 10(7) cells, 50 times more than a recently reported method. Our method can extract total RNA from aerobically grown bacteria and from in vitro hypoxia-induced dormant bacilli and mycobacteria residing within infected macrophages. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Dormant; Hypoxia; Mycobacteria; RNA isolation; Spheroplast; Trizol

Novel screening method based on menadione mediated rapid reduction of tetrazolium salt for testing of anti-mycobacterial agents - Singh, Upasana; Akhtar, Shamim; Mishra, Abhishek; Sarkar, Dhiman (Journal of Microbiological Methods, 2011)
A microplate-based rapid, inexpensive and robust technique is developed by using tetrazolium salt 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) and menadione to determine the viability of Mycobacterium tuberculosis, Mycobacterium bovis BCG and Mycobacterium smegmatis bacilli in microplate format. In general, XTT reduction is an extremely slow process which takes almost 24 h to produce a detectable signal. Menadione could drastically induce this reduction to an almost equal extent within a few minutes in a dose dependent manner. The reduction of XTT is directly proportional to the cell concentration in the presence of menadione. The standardized protocol used 200 mu M of XTT and 60 mu M of menadione in 250 mu l of cell suspension grown either in aerobic or anaerobic conditions. The cell suspension of M. bovis BCG and M. tuberculosis were incubated for 40 min before reading the optical density at 470 nm whereas M. smegmatis was incubated for 20 min. Calculated Signal/Noise (S/N) ratios obtained by applying this protocol were 5.4, 6.4 and 9.4 using M. bovis BCG. M. tuberculosis and M. smegmatis respectively. The calculated Z' factors were > 0.8 for all mycobacterium bacilli indicating the robustness of the XTT Reduction Menadione Assay (XRMA) for rapid screening of inhibitors. The assay protocol was validated by applying 10 standard anti-tubercular agents on M. tuberculosis, M. bovis BCG and M. smegmatis. The Minimum Inhibitory Concentration (MIC) values were found to be similar to reported values from Colony Forming Unit (CFU) and REMA (resazurin microplate assay) assays. Altogether. XRMA is providing a novel anti-tubercular screening protocol which could be useful in high throughput screening programs against different physiological stages of the bacilli. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Menadione; Mycobacterium tuberculosis; Tetrazolium salt; XRMA

Nitrite reductase NirBD is induced and plays an important role during in vitro dormancy of mycobacterium tuberculosis - Akhtar, Shamim; Khan, Arshad; Sohaskey, Charles D.; Jagannath, Chinnaswamy; Sarkar, Dhiman (Journal of Bacteriology, 2013)
Mycobacterium tuberculosis is one of the strongest reducers of nitrate among all mycobacteria. Reduction of nitrate to nitrite, mediated by nitrate reductase (NarGHJI) of M. tuberculosis, is induced during the dormant stage, and the enzyme has a respiratory function in the absence of oxygen. Nitrite reductase (NirBD) is also functional during aerobic growth when nitrite is the sole nitrogen source. However, the role of NirBD-mediated nitrite reduction during the dormancy is not yet characterized. Here, we analyzed nitrite reduction during aerobic growth as well as in a hypoxic dormancy model of M. tuberculosis in vitro. When nitrite was used as the sole nitrogen source in the medium, the organism grew and the reduction of nitrite was evident in both hypoxic and aerobic cultures of M. tuberculosis. Remarkably, the hypoxic culture of M. tuberculosis, compared to the aerobic culture, showed 32- and 4-fold-increased expression of nitrite reductase (NirBD) at the transcription and protein levels, respectively. More importantly, a nirBD mutant of M. tuberculosis was unable to reduce nitrite and compared to the wild-type (WT) strain had a >2-log reduction in viability after 240 h in the Wayne model of hypoxic dormancy. Dependence of M. tuberculosis on nitrite reductase (NirBD) was also seen in a human macrophage-based dormancy model where the nirBD mutant was impaired for survival compared to the WT strain. Overall, the increased expression and essentiality of nitrite reductase in the in vitro dormancy models suggested that NirBD-mediated nitrite reduction could be critical during the persistent stage of M. tuberculosis.

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Analyzing different acetyl co-a metabolizing enzymes as potential drug targets against mycobacterium tuberculosis - Akhtar, Shamim; Singh, Sheetal; Kumar, Santosh; Sarkar, Dhiman (British Microbiology Research Journal, 2015)
Mycobacterium tuberculosis, the causative agent of tuberculosis, is responsible for the deaths of million people around the globe. The scenario is worse than ever due to the emergence of drug resistant strains which are widely spread throughout the globe in much faster ways. To control this worst situation, we need to speed up the search for novel drugs which can specifically kill drug resistant bacteria in collaborative ways amongst academic, clinician and industry. Among different metabolic pathways, fatty acid synthesis pathway has always been a very attractive area for the drug target because of its crucial role during the infection and further in long term survival of pathogen inside the human host. In this review article, we analyzed the role of important and crucial enzymes, which are responsible for the influx and efflux of acetyl co-A substrate, a central hub of metabolites, as potential drug targets against M. tuberculosis.

Probes and techniques used in active and the hypoxia-based dormant state of an antitubercular drug screening assay - Yeware, Amar; Akhtar, Shamim; Sarkar, Dhiman (Medicine in Drug Discovery, 2022)
Current antitubercular drug therapy requires more than six months and is unable to kill latent or dormant forms of tuberculosis. Thus, it is a need of new drug therapy to fight against dormant tuberculosis. However, the major obstacle in the development of novel drugs for dormant tuberculosis is the lack of relevant screening systems and using reliable probes to measure growth inhibition. Until now, several probes used in active state assays are significantly determining the inhibitory effect against the active state of mycobacteria. The dormant condition assays are based on hypoxia-derived dormancy which include resazurin reduction assay, nitrite reductase assay, XTT reduction menadione assay and low oxygen recovery assay. Major probes used in those assays are colorimetric/fluorescent dyes, enzymatic activity, and reporter genes include luciferase and fluorescent proteins. Although these dormant assays are based on hypoxia-induced features and difficult to maintain for a longer duration. Also, they further complicated by growth detection and pursuit of high throughput screening criteria. Here we reviewed complications of probes and assay techniques used for anti-dormant drug screening programs of tuberculosis. This will provide the knowledge to design better alternative drug screening method for the anti-dormant form of tuberculosis.
Keywords: Active and dormant states; and; Drug screening assay; Probes; tuberculosis